PENGARUH PEMBERIAN KONSENTRASI BIOINSEKTISIDA DAUN DAN BIJI MIMBA (Azadirachta indica) TERHADAP KEMATIAN ULAT GRAYAK (Spodoptera litura) - P. S. Ajiningrum; I. A. K. Pramushinta (FMIPA : Universitas PGRI Adi Buana, 2017)
Red spinach (Alternanthera amoena) is one of the vegetable commodities that many people in demand for consumption because of its high nutritional content. Efforts to increase the production of red spinach often experience various obstacles. The main obstacle that limits the productivity of red spinach in the tropics is the number of Plant Disturbing Organisms in the form of pests and potential diseases that can attack and decrease the production of spinach. One of the pests that often attack spinach is the existence of army worm (Spodoptera litura F.). Therefore, farmers need a way to eradicate the pest. This research is experimental using Random Complete Group. The data obtained were analyzed with variant analysis (ANOVA) in one direction and continued with LSD (Least Significant Different) test. Provision of botanical insecticide done by spraying the extract of leaves and seeds mimba with concentration dose 0%, 5%, 10% and 15%. In the final analysis of mortality data of army worm (Spodoptera litura F.) treated with mimba leaf extract obtained significant value of 76.263 at a significant level of 0.05 so it can be concluded that there is influence of mimba leaf extract on mortality of army worm. In the final analysis of mortality data of army worm (Spodoptera litura F.) treated with mimba seed extract obtained significant value of 78.625 at a significant level of 0.05 so it can be concluded that there is an effect of mimba seeds extract on mortality army worm. Keywords: mimba leaf extract, mimba seed extract, red spinach (Alternanthera amoena), army worm (Spodoptera litura F.), botanical insecticide